2013
DOI: 10.33687/phytopath.002.02.0086
|View full text |Cite
|
Sign up to set email alerts
|

Vigor of Plantlet from Microplantlet Treated by Filtrate and Cell Suspension of Some Isolates of Bacillus and Resistance to Banana Wilt Pathogen after Acclimatization

Abstract: Blood Disease Bacterium (BDB) and Fusarium oxysporum f.sp. cubense (FOC) is a couple wilt pathogen  of  banana.  These pathogens are the most important constraint in cultivation of banana in Indonesia.  In the integrated control strategy of the disease, the use of healthy seedlings produced from tissue culture technique is recommended.  The seedling produced by tissue culture technique however leads to lower vigor and susceptibility to the disease due to the aseptic work in vitro causing the beneficial bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The good ability of B subtilis and P. fluorescens, to control the rhizome rot of banana has also been reported by Nagaraj et al [82]. Wiyono and Widono [83] reported that Bacillus species can promote growth as well as induction of resistance to wilt pathogens on tissue culture banana plantlets. Application of plant growth-promoting rihzobacteria (PGPR) on tissue culture banana resulted in high growth rate and vigour in plantlets [84].…”
Section: Colonization Of Microbes In Banana Tissuementioning
confidence: 53%
“…The good ability of B subtilis and P. fluorescens, to control the rhizome rot of banana has also been reported by Nagaraj et al [82]. Wiyono and Widono [83] reported that Bacillus species can promote growth as well as induction of resistance to wilt pathogens on tissue culture banana plantlets. Application of plant growth-promoting rihzobacteria (PGPR) on tissue culture banana resulted in high growth rate and vigour in plantlets [84].…”
Section: Colonization Of Microbes In Banana Tissuementioning
confidence: 53%
“…It has been shown that certain bacterial strains under controlled conditions suppress the growth of F. oxysorum (Ho et al, 2015;Sekhar & Thomas, 2015;Simonetti et al, 2018;Zacky & Tiny, 2013). Within these bacterial groups several strains of the genus Bacillus have been described (Wiyono & Widono, 2013;Xue et al, 2015). This genus, in particular, has been widely studied as a biological control agent due to its multiple mechanisms of antagonistic action such as antibiosis, competition, and the induction of systemic resistance in plants (Chowdhury representar una alternativa más sostenible desde el punto de vista económico y ecológico.…”
Section: Introductionmentioning
confidence: 99%
“…At present disease free quality banana planting material is commercially propagated through tissue culture [6], but in the process of in vitro propagation most of the beneficial endophytic bacteria are also eliminated. Hence, the tissue cultured plantlets are highly and easily susceptible to Fusarium wilt in early stages if proper control measures are not taken up as compared to conventional planting material [7].…”
Section: Introductionmentioning
confidence: 99%